The Textual Thresholds Between Sending And Receiving In The Novel (Diaries Of The Time Of Congestion ) By Saleh Al-Senussi - أنور, مبروكة مفتاح (Tobruk University Journal of Social and Human Sciences, 2022)
The research deals with the textual thresholds (between sending and receiving ) of the novel (Diaries Of Time Of Congestion) by Saleh Al- Sunussi, he is a Libyan novelist from the city of Benghazi, and as is known, the textual thresholds . Or text attachments are what surround the text ,and they are basic procedural keys that the researcher uses to explore the deep issues of the text , and they include thresholds (main headings, sub-headings, author`s name , preface , introduction, and cover plate  ), everything that surround the text ,to clarify its goals and motives for creativity . Hence , we found the textual thresholds of the novel (Diaries Of The Time Of Congestion ) that contain a consensus between the sender and recipient ( the main title , the author`s name, as well as the cover plate and the pictures and colored areas that contain     chains, shadows, baskets handcuffs, skulls crammed , and models )to discovered  the semantic images of the novel , in its treatment of the social , economic, and political issues of a particular country at a  particular time.    This study was dealt with as follows : Introduction: / Preface: / First research: threshold (title) / Second topic: threshold  (author's name) / Third topic:   threshold (cover) / Conclusion / Sources and references.The mechanisms of the integrative approach were adopted in   this study.